The Bane Chronicles - Clareová, Cassandra americká autorka 27. júla 1973; Brennanová, Sarah Rees; Johnsonová, Maureen (Warner Books, Inc, 2015)
The perfect gift for Shadowhunters. This gorgeous illustrated paperback brings the 11 stories about immortal warlock Magnus Bane together in a handy smaller format for the first time. A fan-favourite character from Cassandra Clare's Shadowhunter Chronicles, Magnus features in The Mortal Instruments, The Infernal Devices, Tales from the Shadowhunter Academy and the movie of City of Bones. Magnus will never be able to tell all of his tales. No one would believe him. But these stories shed a little light on his often inscrutable character. They are stories he probably wishes had never got out.